Development of real-time software interface for multicomponent transient signal analysis using Labview and Matlab - Salami, Momoh Jimoh Emiyoka; Tijani, Ismaila; Jibia, Abdussamad Umar (2011)
This paper presents the development of software interface for real-time implementation of the algorithms for multicomponent transient signal analysis. Though, a Matlab-based algorithm has been developed in the previous study on multicomponent signal analysis, real-time signal analysis is required in many practical applications of such signals. Hence, in this study, a user friendly software interface is developed using an integration of Labview and Matlab packages for real-time implementation of the multicomponent signal analysis. The developed software interface was evaluated with experimental fluorescence data collected from a spectrofluorometer system. The results obtained indicate the effectiveness of the integrated software for practical applications.